Squamous cell carcinoma of the anterior tongue: is tumour thickness an indicator for cervical metastasis?. Issue 4 (April 2017) - Loganathan, P.; Sayan, A.; Hsu, D.W.K.; Paraneetharan, S.; Ilankovan, V.
Abstract: The incidence of squamous cell carcinoma (SCC) of the tongue accounts for 90% of all malignancies affecting the oral cavity and oropharynx. The distribution between the anterior and posterior tongue is equal. Nodal metastasis is dependent on various factors including tumour thickness, site, size, differentiation, and perineural and perivascular invasion. There is increasing evidence of a close correlation between tumour thickness and metastasis. A retrospective study covering the 16-year period from 2000 to 2016 was performed. Eighty-one patients with anterior tongue SCC were included. The only primary treatment was surgery. All patients were T1/T2N0M0 stage. Sixty-five patients underwent local excision with simultaneous selective neck dissection; 29 of these patients were confirmed to have occult metastasis. Sixteen patients underwent local excision only as an initial treatment. Four of them subsequently developed neck metastasis within a 6- to 18-month period. The results of this study support recent publications associating tumour thickness with nodal disease. Therefore, it is postulated that prophylactic neck dissection should be considered when the tumour thickness of anterior tongue SCC exceeds 5 mm, in order to prevent lymphatic spread and improve the survival rate.